An attempt to evaluate pressure force on a flapping rigid plate using velocity data of PIV measurements. - Suryadi, Alexandre
The flow field generated by a sinusoidally flapping rigid flat plate was measured using stereo particle image velocimetry to estimate the pressure field on two cross sections of the flapping plate. The pressure field was estimated by integrating the three-dimensional Poisson equation derived from the Euler equation. The solution of this Poisson equation is obtained as a function of the measured phase-averaged velocity field. Simultaneous to PIV measurements, the torque on the flapping axis, which depicts the forces acting on the wing, was measured using strain gauges. The maximum torque coefficients, observed from both methods, of each cycle are delayed from the maximum acceleration of the plate at O=0.25 and O=0.75, with O being the relative phase angle. One of the factors of the phase delay is attributed to the separation of vortex structure along the edges of the plate. After the separation point the increase of pressure drag is delayed relative to the flapping motion, O=0.35. At the same phase, vortex structure is generated on the leeward side of the plate at the free end. Low pressure region was observed on the leeward side of the plate which further adds to the pressure drag.
Keywords: Flapping Wing; Pressure estimation; Stereo PIV; Vortex-structure interaction; Wake-capture.